THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEMS, LEADERSHIP STYLE, WORK MOTIVATION ON EMPLOYEES PERFORMANCE - Endarwati, S; Suhendro, s; Dewi, R. Riana (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2018)
This study aims to test and analyze the effect of accounting information systems, leadership style and work motivation on performance garment company employees in sukoharjo.The population used in this research is the garment company employees at the accounting work on PT Danliris, PT Sunwoo Indonesia, and PT Panji Anom Setia in sukoharjo. Methods of data analysis used in this study is by purposive sampling. the number of respondents in this study as many as 38 of the 45 respondents number of questionnaires presented. Methods of analysis used was multiple linear regression analysis. The results showed that the accounting information system variables and influential work motivation and significantly to the variable performance of employees.  While variable leadership style has no effect against variable employee performance. the determination coefficients (R2) of 0.415. This indicates that variansi on a variable performance practice undertaken by the company in Sukoharjo garment amounted to 41.5% can be explained by the variable accounting information systems, leadership style and work motivation, whereas the remaining 58.5 % explained by factors – factors other than that examined